Tectonic Aspects of the East Anatolian 06.02.2023 Earthquake in Turkiye - Celik, Hasan; Trikhunkov, Ya. I.; Sokolov, S. A.; Trifonov, V. G.; Zelenin, E. A.; Karginoglu, Yusuf; Bachmanov, D. M. (Pleiades Publishing Ltd, 2023)
During the East Anatolian earthquake with M-w = 7.8, which occurred on February 6, 2023 at 1:17 UTC, the 361 km long segment of the NE-trending East Anatolian active left-lateral fault zone (EAFZ) was activated. A left-lateral displacement took place at a distance of 318 km on formed seismic ruptures. Its maximum magnitude of 8.5 m is registered northward of the earthquake epicenter. To the northeast, the displacement of several meters is maintained over a significant length of the activated segment and is accompanied by uplift of the south-eastern side of the ruptured zone at up to 1.5 m. To the southwest of the maximum displacement area, the strike slip decreases from it at shorter distances compared to the northeastern part and the vertical component varies, although the southeastern side is mostly uplifted. In the terminal southwest, the strike slip is replaced by normal faults, gaping fractures, and other manifestations of transverse extension, which are accompanied by landslides and are mainly secondary seismic dislocations. Left lateral slip also occurred at the northern ends of the western and eastern branches of the Dead Sea Transform (DST), adjacent to the EAFZ from the south. Despite the fact that the energy distribution of numerous aftershocks along the EAFZ is generally proportional to the distribution of offsets on seismic ruptures, the slip on the EAFZ occurred during and immediately after the main shock. In the northern part of the DST, a significant decrease in the amount of energy released by strong earthquakes during the last centuries has been established. We consider that the tectonic stress accumulated in the northern part of the DST became the important geodynamic source of the East Anatolian 02.06.2023 earthquake.
Keywords: East Anatolian earthquake; East Anatolian active fault zone; Dead Sea Transform; seismic ruptures and offsets; left-lateral fault; aftershocks; accumulation of tectonic stress